4명 이하 사업장에 대한 근로기준법 적용확대 방안 연구 - 정찬영 (The Graduate School, Ajou University, 2024)
4명 이하 사업장에 대한 근로기준법 적용확대 방안 연구 아주대학교 대학원 법 학 과 정 찬 영 1953년 근로기준법이 제정된지 70년이 지났음에도 상시 4명 이하 사업 또는 사업장(이하 ‘4명 이하 사업장’이라 한다)에는 아직도 적용제외되는 법 규정이 남아 있다. 해고 등의 제한(제23조), 근로시간(제50조), 연장 근로의 제한(제 53조), 연차 유급휴가(제60조) 등 주요 근로조건이 적용되지 않고 있다. 2021년말 기준 4명 이하 사업장에 종사하는 근로자는 314만 명으로서 전체 근로자 중 17.3%를 차지한다. 4명 이하 사업장의 근로자는 상대적으로 권리보 호가 더 필요함에도 근로기준법의 일부 규정을 적용제외하고 있다. 그 동안 여러 차례 근로기준법 개정을 통해 적용범위를 꾸준히 확대해 왔지만 구체적 기준 없이 근로기준법시행령의 적용범위를 조정하는 방법으로 이루어졌다. 그간 근로기준법의 적용제외 사유는 (ⅰ) 사업주의 법 준수능력 부족, (ⅱ) 정부의 감독행정능력 부족, (ⅲ) 경영 부담으로 인한 경제계의 반발 등이었다. 그러나 근로기준법 제정 이래 산업구조를 비롯한 정치·사회·경제적인 측면에서 많은 변화가 있었다. 그럼에도 사용자의 법 준수 및 정부의 감독행정상의 능력 부족 등이 여전히 적용제외 사유인지를 재검토할 필요가 있다. 현행 근로기준법이 다양한 업종별·직업별 특성을 반영하지 못하고, 사업장 규모에 따라 일률적인 법적용에 따른 법의 실효성 문제도 검토해야 한다. 근로기준법의 적용범위와 관련한 대부분의 선행연구는 원칙적으로는 모든 사업장에 대한 전면적인 근로기준법을 적용하는데 동의하고 있다. 그러나 한편으로는 전면적인 적용의 한계와 문제점으로 단계적인 적용의 불가피성을 논하고 있다. 국회 근로기준법 개정안 발의도 전면 적용을 비롯한 일부 법조항의 확대적용까지 다양하다. 현행 근로기준법상 적용 제외되는 모든 법 조항을 4명 이하 사업장에 전면 적용하는 것은 여러 가지 측면을 고려할 때 사실상 어렵다고 본다. 그 중에는 노사단체 및 이해관계자간의 입장차로 대변되는 사회적 환경이나 업종이나 근로자의 직업 특성을 반영하지 못하는 제조업 근간의 근로기준법 체계의 문제도 있다. 본 연구에서는 4명 이하 사업장에 근로기준법 적용범위 확대적용을 검토함에 있어서 현실적인 사회·경제적 여건 등을 고려해 법 실효성을 담보할 수 있는 합리적인 적용확대 방안을 강구하고자 한다. 이를 위해 먼저 근로기준법의 적용범위와 관련한 기본개념을 정리하고, 근로기준법의 적용범위의 연혁 및 배경 등을 알아보기 위하여 일제 강점기의 노동법령부터 제정근로기준법, 개정 근로기준법 변천사를 자세히 살펴보았다. 근로기준법 적용범위와 관련된 국회의 회기별 개정 발의안과 검토안을 살펴보았다. 정부, 노동계, 경영계 등의 입장도 비교 검토해 보았다. 외국 입법에서는 국제연합, 국제노동기구 등 국제기준과 일본, 미국, 독일, 프랑스의 노동관계법의 규율방식 및 적용범위, 예외적인 법적용 사례를 살펴보았다. 또한 그간의 적용제외 사유인 사업장의 법준수능력 및 감독행정능력의 부족이 여전히 유효한지 를 검토했다. 그리고 전체 적용제외 법조항의 내용 및 적용제외 관련 쟁점과 문제점 등을 검토했다. 근로기준법의 적용범위 확대방안에는 여러 접근방식이 있다, 현행 근로기법 체계에서 다양한 업종 및 직업군을 포섭하여 근로자를 촘촘하게 보호하기에는 근로기준법의 체계상 한계가 있다. 이러한 한계를 감안하여 현실에서 적용 가능하면서 부작용을 최소화 할 수 있는 4명 이하 사업장의 근로기준법 적용범위 확대 방안을 제시했다. 근로기준법의 적용확대에 대한 기본방향은 전면확대를 원칙으로 하되, 우선 순위에 의한 1단계 적용, 경과규정을 둔 2단계 적용, 제도개선 등을 거친 3단계 적용 방안을 제시했다. 적용범위 확대를 위해 현실적인 건을 고려하고 구체적인 기준에 따라 법 적용 대상의 우선 순위를 정하였다. 4명 이하 사업장 근로자의 법정근로기준을 보호하기 위하여 근로기준법의 적용범위를 확대하는 것도 중요하지만, 향후 사업의 특성이나 근로자가 수행하는 업무의 특수성을 반영할 수 있는 법체제가 마련되어야 한다. _x000D_ ** 주제어 : 근로기준법의 적용범위, 적용제외, 적용범위 확대, 4명 이하 사업장, _x000D_ 영세사업장, 법정근로조건|A Study on the Expansion Application of the Labor Standards Act to Workplaces with 4 or fewer Employees Jeong Chan-young Department of Law Graduate school of Ajou university_x000D_ Seventy years have passed since the enactment of the Labor Standards Act in 1953, but there are still legal provisions that are exempt from the application of businesses or workplaces with four or fewer employees at any given time (hereinafter referred to as "workplaces with four or fewer employees"). Major working conditions such as restrictions on dismissal (Article 23), working hours (Article 50), restrictions on overtime (Article53), and annual paid leave (Article 60) do not apply. As of the end of 2021, there were 3.14 million workers in businesses with four or fewer employees, accounting for 17.3% of the total workforce. orkers in workplaces with four or fewer employees are exempt from some provisions of the Labor Standards ct, even though they need to protect their rights comparatively. In the meantime, the scope of application has been steadily expanded through several amendments to the Labor Standards Act, but it has been done by adjusting the scope of application of the Enforcement Decree of the Labor Standards Act without specific standards. Until now, the reasons for exemption from the Labor Standards Act have been (i) the employer's inability to comply with the law, (ii) the government's lack of ability to supervise and administer, and (iii) the backlash from the business community due to the burden on management. However, since the enactment of the Labor Standards Act, there have been many changes in political, social, and economic aspects, including the industrial structure. Nonetheless, it is necessary to re-examine whether the user's compliance _x000D_ with the law and the government's lack of ability to supervise and administer the law are still grounds for exemption. The current Labor Standards Act does not reflect the characteristics of various industries and occupations, and the issue of the effectiveness of the law due to the uniform application of the law according to the size of the workplace should also be examined. _x000D_ Most of the previous studies on the scope of application of the Labor Standards Act agree in principle that the Labor Standards Act should be applied comprehensively to all workplaces. However, on the other hand, the inevitability of step-by-step application is discussed as a limitation and problem of full-scale application. The National Assembly's proposal to amend the Labor Standards Act also ranges from full application to the expanded application of some legal provisions.It is difficult to fully apply all the provisions of the law that are excluded under the current Labor Standards Act to workplaces with four or fewer employees, considering several aspects. Among them, there is the problem of the social environment represented by differences in positions between labor-management organizations and stakeholders, and the problem of the _x000D_ labor standards law system based on the manufacturing industry, which does not reflect the characteristics of the industry or the occupation of workers. In this study, in examining the expansion of the scope of application of the Labor Standards Act to workplaces with four or fewer employees, we will consider realistic socio-economic conditions and find a reasonable application expansion improvement plan to ensure the effectiveness of the To this end, we first summarized the basic concepts related to the scope of application of the Labor Standards Act, and in order to understand the history and background of the scope of application of the Labor Standards Act, we took a closer look at the history of the labor laws and regulations of the Japanese Colonial Period, the enacted Labor Standards Act, and the changes in the revised Labor Standards Act. We examined the proposals and reviews of the National Assembly's amendments to the scope of applicationㅍof the Labor Standards Act by session. The positions of the government, labor, and business circles were also compared. In foreign legislation, international standards such as the United Nations and the International Labor Organization, as well as the methods and scope of regulation and application of labor relations laws in Japan, the United States, Germany, and France, and exceptional cases of application of the law were examined. In addition, it examined whether the lack of legal compliance and supervisory administrative capacity of the workplace, which was the reason for the exemption, is still valid. In addition, the contents of the entire exemption law and the issues and problems related to the exemption were reviewed. There are various approaches to expanding the scope of application of the Labor Standards Act, and there are limitations in the system of the Labor Standards Act to protect workers by encompassing various industries and occupational groups in the current Labor Standards Act system. Considering these limitations, we proposed a plan to expand the scope of application of the Labor Standards Act to workplaces with four or fewer employees that can be applied in reality and minimize adverse effects. The basic direction for expanding the scope of application of the Labor Standards Act is based on the principle of comprehensive expansion, but the first stage of application by priority, the second stage with transitional regulations, and the third stage of application through system improvement were proposed. In order to expand the scope of application, realistic conditions were taken into consideration and the priority of the subjects of the law was determined according to specific criteria.While it is important to expand the scope of application of the Labor Standards Act in order to protect the statutory labor standards of workers in workplaces with four or fewer employees, a legal framework should be prepared that can reflect the characteristics of the business and the specificity of the work performed by workers in the future. _x000D_ Key words: Scope of application of the Labor Standards Act, exemption, _x000D_ expansion of the scope of application, workplaces with 4 or _x000D_ fewer employees, small businesses, legal working conditions
학위논문(박사)--법학과,2024. 2
Keywords: 4명 이하 사업장; 근로기준법의 적용범위; 법정근로조건; 영세사업장; 적용범위 확대; 적용제외